Favouritism: exploring the ‘uncontrolled’ spaces of the leadership experience - Palermo, O. A.; Carnaz, A. C.; Duarte, H. (Leadership, 2019)
In this paper, we argue that a focus on favouritism magnifies a central ethical ambiguity in leadership, both conceptually and in practice. The social process of favouritism can even go unnoticed, or misrecognised if it does not manifest in a form in which it can be either included or excluded from what is (collectively interpreted as) leadership. The leadership literature presents a tension between what is an embodied and relational account of the ethical, on the one hand, and a more dispassionate organisational ‘justice’ emphasis, on the other hand. We conducted 23 semi-structured interviews in eight consultancy companies, four multinationals and four internationals. There were ethical issues at play in the way interviewees thought about favouritism in leadership episodes. This emerged in the fact that they were concerned with visibility and conduct before engaging in favouritism. Our findings illustrate a bricolage of ethical justifications for favouritism, namely utilitarian, justice, and relational. Such findings suggest the ethical ambiguity that lies at the heart of leadership as a concept and a practice.